DNA metabarcoding reveals that 200‐μm‐size‐fractionated filtering is unable to discriminate between planktonic microbial and large eukaryotes. (3rd February 2017) - Liu, Lemian; Liu, Min; Wilkinson, David M.; Chen, Huihuang; Yu, Xiaoqing; Yang, Jun
Abstract: Microeukaryotic plankton (0.2–200  μ m) are critical components of aquatic ecosystems and key players in global ecological processes. High‐throughput sequencing is currently revolutionizing their study on an unprecedented scale. However, it is currently unclear whether we can accurately, effectively and quantitatively depict the microeukaryotic plankton communities using traditional size‐fractionated filtering combined with molecular methods. To address this, we analysed the eukaryotic plankton communities both with, and without, prefiltering with a 200  μ m pore‐size sieve –by using SSU rDNA‐based high‐throughput sequencing on 16 samples with three replicates in each sample from two subtropical reservoirs sampled from January to October in 2013. We found that ~25% reads were classified as metazoan in both size groups. The species richness, alpha and beta diversity of plankton community and relative abundance of reads in 99.2% eukaryotic OTUs showed no significant changes after prefiltering with a 200  μ m pore‐size sieve. We further found that both >0.2  μ m and 0.2–200  μ m eukaryotic plankton communities, especially the abundant plankton subcommunities, exhibited very similar, and synchronous, spatiotemporal patterns and processes associated with almost identical environmental drivers. The lack of an effect on community structure from prefiltering suggests that environmental DNA from larger metazoa is introduced into the smaller size class. Therefore, size‐fractionated filtering with 200  μ m is insufficient to discriminate between the eukaryotic plankton size groups in metabarcoding approaches. Our results also highlight the importance of sequencing depth, and strict quality filtering of reads, when designing studies to characterize microeukaryotic plankton communities.